Ontologi, Epistemologi, dan Aksiologi Dalam Filsafat Islam Sebagai Fondasi Pendidikan Moral - Rahmaniah; Muhammad kenzie Zuhdi Ariqo; Naifatin Nurfaiq Alsalsabila; M.Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study explores the relationship between philosophy, education, and Islamic teachings in understanding human nature and establishing a moral foundation for the modern era. The research aims to clarify how ontology, epistemology, and axiology shape the framework of Islamic education. Using a library research method, the study examines classical and contemporary philosophical works alongside Islamic scholarly writings to construct relevant conceptual insights. The findings reveal that ontology views humans as rational and spiritual beings who carry ethical responsibilities as stewards of the earth. Epistemology demonstrates that knowledge emerges from reason, empirical experience, and divine revelation. Meanwhile, axiology emphasizes that knowledge must be directed toward moral values, making education responsible not only for intellectual development but also for moral character. Overall, this research affirms that integrating philosophical principles with Islamic values provides a solid foundation for understanding humanity, truth, and educational aims in the contemporary context.